Reflexivity, methodology and contexts in participatory digital media research: making games with Latin American youth in London - Paula, Bruno de (Learning, Media and Technology, 2021)
In this paper, I intend to explore the role played by reflexivity in grounding a more critical perspective when designing, implementing and analysing participatory digital media research. To carry out this methodological reflection, I will present and discuss a recently concluded research project on young people’s game-making in an after-school programme targeting Latin American migrants in London/UK. I will pay special attention to how my subjectivities influenced planning, data generation and analysis of this programme, and to how context, lived experiences, curricular decisions and interpersonal relationships shaped the kinds of knowledge produced through this research. Findings emerging from this experience included relevant dissonances between curricular design/decisions and the use of participatory approaches in game-making, and the limitations of traditional analytical categories within the Social Sciences field (e.g., gender and intersectionality) to understanding subjectivities expressed through game-making. This study offers relevant insights into the place of reflexivity in research on digital media production by young people by highlighting its complexity and by calling for more critical and less homogenising approaches to this type of research.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Korean Soap Operas, Telenovelas and Sci-fi Conspiracies: A Game-making Experience with Latin American Youth in London - Paula, Bruno de (Digital Culture and Education, 2021)
This paper explores a game-making programme for 14 Latin American migrants aged 13-18 in London/UK, carried out between October/2017-January/2018, where I investigated the relationships between game conventions, platforms and personal preferences in the curation of fluid identities through game production. Participants presented varying levels of affinity with games linked both to access issues and to other specific elements (e.g. perception of games in contemporary culture, gender). Questionnaires, observations, unstructured/semistructured interviews and gaming archives were employed to explore this participatory initiative and data was analysed through Multimodal Sociosemiotics. Findings remarked how shared understandings about digital games can find their way into platforms and act as “cultural-technical gatekeepers”, supporting or hindering the engagement with game-making of those often perceived as outsiders to gaming culture. This gatekeeping happens when there are “creative dissonances” between, for example, personal preferences and platforms aligned to normative/mainstream genres. These dissonances, however, can end up fostering subversive designs, contravening gaming conventions and potentially challenging traditional gaming boundaries. This insight is relevant for understanding “cultural-technical constraints” and subversive/non-mainstream game-making, especially in relation to innovation and appropriation of game-making resources/strategies by non-mainstream groups.
Keywords: 1-Jeux vidéo; 1-TV; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

La (dé)mythification de l’artiste colombien MIGUEL ÁNGEL ROJAS ET JOSÉ ALEJANDRO RESTREPO - de la Cruz Lichet, Virginia (Revue Proteus, 2019)
Depuis quelques décennies, certains artistes colombiens cherchent à repenser ce que peut être aujourd’hui l’identité colombienne, et plus concrètement celle de l’artiste. Au-delà du stéréotype de ce qu’est le « Colombien » vu de l’extérieur, au-delà d’une histoire coloniale – et toutes ses problématiques – commune aux pays d’Amérique latine, ainsi que d’une histoire récente plus particulière connue pour son extrême violence, nous pouvons affirmer que l’identité colombienne est le résultat d’identités multiples, diverses et variées. Par ailleurs, il existe un dénominateur commun qui peut la définir car elle s’est construite durant ces deux derniers siècles à partir d’un concept : celui de « l’hybridité ».
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Postcolonial/Décolonial: La preuve par l'art - Toussaint, Évelyne (Presses universitaires du Midi, 2021)
"Les liens entre l'art contemporain et les questions de colonialité, postcolonialité, et décolonialité sont anciens et multiples. Des artistes occidentaux et non-occidentaux, depuis plusieurs décennies déjà, s'en sont emparés pour produire des œuvres qui témoignent de leurs engagements politiques, sociétaux et esthétiques. Des concepts que les études postcoloniales ont approfondies ou inventées – agency (agentivité), mimicry (mimétisme/simulacre), ou essentialisme stratégique –, en autant d'outils utiles à démêler la complexité des relations coloniales et, au-delà, de toutes les relations de domination, sont ainsi revisités par les artistes. D'autre part, des auteurs, relevant de ces champs d'études qui conservent aujourd'hui toute leur actualité politique et leur pertinence théorique, disent à leur tour l'intérêt qu'ils portent à la création contemporaine. Associant vingt historiens de l'art et chercheurs en littérature, philosophie, droit ou psychanalyse, Postcolonial/Décolonial. La preuve par l'art présente des travaux portant sur des démarches artistiques (Betye Saar, Fred Wilson, Sarkis, Lidwien van de Ven, Voluspa Jarpa, des artistes du collectif Mira au Mexique, Iris Kensmil, Jean Renoir, et bien d'autres), mais aussi sur des propositions institutionnelles (notamment initiées par le Centro de Arte y Comunicación de Buenos Aires, la Biennale de Venise ou le Van Abbemuseum d'Eindhoven), associées en de nouveaux réseaux de solidarités. Une place particulière est réservée aux singularités artistiques, théoriques et juridiques en Amérique latine, lieu d'émergence des théories décoloniales. Sous un angle historiographique et épistémologique, on trouvera ici des analyses des fondements historiques, théoriques et idéologiques du postcolonial dont les théorisations, loin de la saturation conceptuelle dont certains veulent les accuser, concernent particulièrement l'histoire de l'art. "
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé